To study medical students’ perspective on rising violence against doctors. Do they consider obstetrics and gynecology a risky branch? - Sood, Reena; Singh, Gurmeet; Arora, Parvinder Kaur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: In recent years, there has been an epidemic of violence against health professional in many nations including India. The Indian Medical Association (IMA) has reported that 75% of doctors have faced physical or verbal violence during their lifetime. The objective of present study was to evaluate the medical student perspective on rising violence against doctors. Methods: This is a cross sectional questionnaire based study carried out at Sri Guru Ram Das Institute of medical Sciences and Research Amritsar. Undergraduate medical students from second year onwards, interns and post- graduate students of the institution were included in the study. Data was compiled and statistically analysed. Results: Total 497 medical students participated in the study. Among participants 327 (65.8%) were undergraduates, 106 (21.3%) were interns, 64 (12.9%) were postgraduate students 97.18% of students said that they were aware of rising incidents of violence against doctors. while 96% of participants said that they were concerned about the problem. For 86.1% students source of information of these incidents was social media. 82.5% participants said that doctors are at higher risk of being victim of violence than other profession. 89.1% of participants who had said that doctors are at higher risk of being victims of violence than other professions have said yes to the question that doctors need to be trained in martial arts. 70.2% said that these incidences would affect their future carrier choices. 60.8% Students said that certain specialties are more prone to receive violence than others. In response to an open-ended question which specialties are more prone, 83.6% participants had written surgical branches and obstetrics and gynecology. Conclusions: The study indicates that they find certain specialties more-risky and their inclination towards non- surgical branches for post-graduation.